2020
DOI: 10.1111/apa.15392
|View full text |Cite
|
Sign up to set email alerts
|

Relative age is associated with bullying victimisation and perpetration among children aged eight to nine

Abstract: Bullying is defined by the American Centers for Disease Control and Prevention as unwanted repetitive aggressive behaviour that occurs within an unequal power relationship and inflicts harm or distress on the victim. 1 The prevalence of involvement in bullying is approximately 20%-25%. 2 It has possible long-lasting negative impacts such as mental 3-7 and physical health problems, socioeconomic disadvantages, 5 and criminality. 4,5 Bullies have been shown to demonstrate proactive aggression and be motivated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
4
1
Order By: Relevance
“…Regarding White adolescents, of the individual‐level correlates of bullying, younger age was found to be negatively associated with peer victimization, which was similar to some findings (Dinkes, Kemp, Baum, & Snyder, 2009) and contrary to others (Tiiri et al, 2020). However, studies have shown that bullying tends to increase as youth grow older (Hong & Espelage, 2012).…”
Section: White Adolescentssupporting
confidence: 84%
“…Regarding White adolescents, of the individual‐level correlates of bullying, younger age was found to be negatively associated with peer victimization, which was similar to some findings (Dinkes, Kemp, Baum, & Snyder, 2009) and contrary to others (Tiiri et al, 2020). However, studies have shown that bullying tends to increase as youth grow older (Hong & Espelage, 2012).…”
Section: White Adolescentssupporting
confidence: 84%
“…This age is adolescent age which is reported to be the bullying victims and can cause high suicide cases (5). This study's results contradict another study that states that the youngest children more easily become victims (6). It is possible that bullying occurs in all age ranges.…”
Section: Discussioncontrasting
confidence: 65%
“…This shows that young children are exposed to various types of bullying by older children, such as exclusion, emotional violence and physical violence. Similarly, in the study of Tiiri et al (2020), relatively younger children are more likely to be bullied than those in the older age group. The effects of starting school at an early age are manifested not only in the primary school period, but also in later years such as secondary school and high school.…”
Section: Findings Discussion and Resultsmentioning
confidence: 94%